The relationship between serum eosinophil peroxidase and major basic protein levels in relation to severity and response to H1 antihistamines in chronic spontaneous Urticaria - Cuc Thi Kim Nguyen; Lan Thi Pham; My Huyen Le; Doanh Huu Le; Minh Nguyet Vu (PLoS ONE, 2025)
Objective In chronic spontaneous urticaria (CSU), the significance of serum Eosinophil Peroxidase (EPO) and Major Basic Protein (MBP) levels as indicators of disease severity and response to antihistamine treatment is currently inadequately understood. This study explores the correlation between serum EPO and MBP levels, the severity of the disease, and the efficacy of antihistamines in patients with CSU. Methods A cross-sectional study involved 120 CSU patients alongside 30 healthy controls. In addition, a cohort study targeted 60 patients diagnosed with severe CSU, defined by a Urticaria Activity Score over 7 days (UAS7 ≥ 28). Initially, these patients received a dose of 20 mg of bilastine, which could be increased to a maximum of 80 mg depending on the results of the Urticaria Control Test (UCT) conducted on days 15, 30, and 60. Baseline serum concentrations of EPO and MBP were assessed for all participants, with follow-up measurements conducted after two months for those with severe CSU utilizing an ELISA kit.. Results Serum EPO concentration in the severe CSU group was similar to that in the non-severe group (P = 0.33) and was higher than that in the healthy control group (P < 0.001). Serum MBP concentrations did not differ among these three groups (P = 0.19). Serum EPO and MBP concentrations did not correlate with UAS7 and UCT. They did not differ among antihistamine response groups in the severe CSU group (P > 0.05) and decreased after 2 months of antihistamine treatment (P < 0.05). Conclusions Serum EPO and MBP levels are neither biomarkers predicting CSU severity nor factors predicting response to antihistamine in the severe group. This lack of association may help explain why treatments targeting eosinophil proliferation and chemotaxis have not been successful in clinical trials for patients with antihistamine-refractory CSU.